2017
DOI: 10.1371/journal.pone.0177677
|View full text |Cite
|
Sign up to set email alerts
|

Raman-microscopy investigation of vitrification-induced structural damages in mature bovine oocytes

Abstract: Although oocyte cryopreservation has great potentials in the field of reproductive technologies, it still is an open challenge in the majority of domestic animals and little is known on the biochemical transformation induced by this process in the different cellular compartments. Raman micro-spectroscopy allows the non-invasive evaluation of the molecular composition of cells, based on the inelastic scattering of laser photons by vibrating molecules. The aim of this work was to assess the biochemical modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In contrast, the addition of ɛ-ACA resulted in a significant decrease in cleavage (59.20 ± 3.10%) and blastocyst rates (21.85 ± 4.46%; p < .05, Figure 4). and phenylalanine (Phe,~1605 and~1000 cm −1 ) described by other authors (Bogliolo et al, 2013(Bogliolo et al, , 2014Rizo et al, 2016;Rusciano et al, 2017) were detected (Table 2). In a global analysis, it should be noticed that the spectral profile obtained from oocytes in the SK group showed high intense protein bands similar to the control spectrum.…”
Section: Effect Of Sk or ɛ-Aca On The Developmental Competence Of Bmentioning
confidence: 51%
See 2 more Smart Citations
“…In contrast, the addition of ɛ-ACA resulted in a significant decrease in cleavage (59.20 ± 3.10%) and blastocyst rates (21.85 ± 4.46%; p < .05, Figure 4). and phenylalanine (Phe,~1605 and~1000 cm −1 ) described by other authors (Bogliolo et al, 2013(Bogliolo et al, , 2014Rizo et al, 2016;Rusciano et al, 2017) were detected (Table 2). In a global analysis, it should be noticed that the spectral profile obtained from oocytes in the SK group showed high intense protein bands similar to the control spectrum.…”
Section: Effect Of Sk or ɛ-Aca On The Developmental Competence Of Bmentioning
confidence: 51%
“…Figure 6 shows the spectral profiles of the four groups truncated in the region between 1800 and 800 cm −1 . Characteristic bands of proteins such as amide I (AmI, ~1656 cm −1 ) mode, amide III (AmIII, region 1320–1260 cm −1 ) mode and the signals assigned to the vibrations of aromatic amino acids of the aromatic rings of tyrosine (Tyr, ~1616 cm −1 ) and phenylalanine (Phe, ~1605 and ~1000 cm −1 ) described by other authors (Bogliolo et al, 2013, 2014; Rizo et al, 2016; Rusciano et al, 2017) were detected (Table 2). In a global analysis, it should be noticed that the spectral profile obtained from oocytes in the SK group showed high intense protein bands similar to the control spectrum.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Unless otherwise stated, all reagents were purchased from Sigma-Aldrich (Johannesburg, South Africa). Mediums used for IVF culture procedures were based on protocols used by the Department of Veterinary Medicine and Animal Reproduction, Federico II University, Naples, Italy [21,22]. In short, the aspiration medium was TCM 199 medium consisted of Synthetic Oviduct Fluid (SOF) medium [24] with 30 µL/mL essential amino acids and 10 µL/mL non-essential amino acids.…”
Section: Reagents and Mediamentioning
confidence: 99%
“…It has been demonstrated that vitrification solution could induce zona hardening and biochemical changes in zona pellucida (ZP) in mammalian oocytes (Bogliolo et al, ; Larman, Sheehan, & Gardner, ). Oocyte structure and competence can be also influenced by high concentrations of cryoprotective agents (CPAs) required to achieve a glass‐like state in vitrification (Devi & Goel, ; Ezoe et al, ; Liu et al, ; Rusciano et al, ). Since the time when the first live offspring was obtained from cryopreserved domestic oocytes (Hamano, Koikeda, Kuwayama, & Nagai, ), a limited number of studies has reported high developmental rate of vitrified‐warmed ovine oocytes.…”
Section: Introductionmentioning
confidence: 99%